The informal caregiver experience in Colombia: A systematic review and meta-synthesis - Torres-Sanmiguel, Andres Felipe; Carreño-Moreno, Sonia; Chaparro-Diaz, Lorena (Universidad y Salud, 2023)
Introduction: Caregivers have a particular way of experiencing their caring roles. They have to adapt to a health system that does not recognize them as subjects of care and, at the same time, makes them responsible for tasks for which they are not prepared, without any support. Objective: To incorporate primary studies findings into a qualitative meta-synthesis to describe informal caregivers experience in Colombia. Materials and methods: Systematic review of qualitative literature. A systematic search was carried out using meta-search engines with the following descriptors: caregivers; experience; qualitative research; and Colombia. The study selection followed the PRISMA methodology and the COREQ tool, which is available on the EQUATOR network. Results: 20 qualitative studies were included, which were encoded with 250 nominal codes and classified in 6 central categories: relationship between the dyad and its context; hitting rock bottom to strengthen spiritually; commitment; overprotection and self-limitation; key moments to adapt to the caregiving task; relationship with self; health system; policies and institutional support. Conclusion: Caregivers share the illness experience with their loved ones. The health system needs to change in order to meet the needs of the dyads rather than the needs of the sick of disabled.